Method for preparing efficient copper-indium-gallium-sulfur-selenium solar cell by doping antimony based on solution method
By adding different concentrations of metal antimony salt doping and spin coating annealing technology to the precursor solution, the problem of poor quality of copper indium gallium selenide solar cell film preparation is solved, and efficient copper indium gallium selenide sulfur absorption is achieved Layer preparation and efficiency improvement, facilitate large-scale commercialization.
Patent Information
- Application Number
- CN202411304752.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The existing thin film quality of copper indium gallium selenide solar cells based on non-hydrazine solutions is poor, which limits the improvement of device efficiency, and is complex in the preparation process and high in cost, making it difficult to achieve large-scale commercialization.
By adding different concentrations of metal antimony salts to the precursor solution for antimony doping, spin coating and multiple annealings, a copper indium gallium selenide sulfur absorbing layer penetrated through the micron level is obtained, which simplifies the preparation process and reduces production costs.
The preparation of a high-quality copper indium gallium selenide sulfur absorber layer has been achieved, which has significantly improved the efficiency of the solar cell to reach 16.33%, and simplified the production process to facilitate large-scale commercial application.
Smart Images

Figure CN119208442A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of application of optoelectronic device technology, and more specifically, relates to a method for preparing high-efficiency copper indium gallium sulfur selenide solar cells by antimony doping based on a solution method. Background Art
[0002] With the increasing global concern about climate change, reducing carbon emissions and achieving carbon neutrality has become a common mission for all countries. Against this grand background, the photovoltaic industry stands out with its unique advantages and becomes a key force in achieving sustainable development. Polycrystalline chalcopyrite copper indium gallium selenide (CIGS) material has excellent optoelectronic properties, including adjustable band gap, high absorption coefficient, and high stability, making it an ideal photovoltaic material in photovoltaic applications.
[0003] In recent years, the efficiency of copper indium gallium selenide thin film solar cells prepared by solution has exceeded 15%, reaching the minimum value for commercial application. Among them, the preparation of copper indium gallium selenide (CIGS) absorption layer based on hydrazine solution presents an absorption layer that penetrates the grains up and down, similar to the vacuum method, so the efficiency is generally high. However, the hydrazine solution is highly toxic, and the solution is extremely unstable in the air, which undoubtedly limits the further large-scale development of the solution system. The use of non-hydrazine solution to prepare copper indium gallium selenide (CIGS) often requires a high-temperature selenization process. Due to the limited downward uptake of selenium by selenization and the residual organic impurities, the absorption layer obtained by selenization eventually presents upper and lower stratification, resulting in low efficiency of the final copper indium gallium selenide (CIGS) device. In order to solve the above problems, the following solutions are currently mainly used: first, increase the Cu / In in the precursor solution, but this method often requires additional etching steps in the final film; second, introduce alkali metal elements M (M = Li, Na, K, Rb, Cs); third, introduce Ag elements. However, the absorption layer obtained by the above method still has the problem of poor quality of the prepared product, which limits the improvement of device efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method, aiming to solve the technical problem that the quality of the prepared film is poor in the existing preparation technology based on non-hydrazine solution, which limits the improvement of device efficiency.
[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method, comprising the following steps:
[0006] Preparing a precursor solution;
[0007] Adding different amounts of metal antimony salts to the precursor solution for antimony doping;
[0008] Spin coating a precursor solution and performing multiple annealing operations to obtain a precursor film;
[0009] After selenization treatment, a copper indium gallium selenide sulfur absorption layer is obtained;
[0010] A buffer layer, a window layer and an electrode are deposited to prepare an antimony-doped copper indium gallium selenide sulfur thin film solar cell.
[0011] Preferably, the preparation of the precursor solution comprises:
[0012] Weigh thiourea, copper acetate, indium trichloride tetrahydrate, and anhydrous gallium chloride respectively according to a preset ratio;
[0013] Thiourea, copper acetate, indium trichloride tetrahydrate and anhydrous gallium chloride are sequentially added into a dimethylformamide solvent to obtain a CIGS precursor solution.
[0014] Preferably, the molar ratio of thiourea to the sum of all metal salts is 2.5-3.
[0015] Preferably, the step of adding a metal antimony salt to the precursor solution for antimony doping, thereby preparing a CIS precursor solution with different doping concentrations, comprises:
[0016] Antimony trichloride is added to the prepared solution. Antimony doping in the precursor solution is achieved by adding different amounts of antimony trichloride, and the molar concentration range of antimony trichloride is 0-0.035M.
[0017] Preferably, antimony doping in the precursor solution is achieved by adding different amounts of antimony trichloride, wherein the molar ratio of antimony trichloride to copper acetate is 0, 2%, 5% and 8%.
[0018] Preferably, the spin coating of the precursor solution and the annealing and drying operation are repeated multiple times to obtain a precursor film, comprising:
[0019] During each spin coating annealing process, hot stage annealing and drying are adopted, the spin coating speed is 2000-3500rpm, and the hot stage annealing temperature is 250-300℃.
[0020] Preferably, the spin coating of the precursor solution and the annealing operation are repeated multiple times to obtain the precursor film, including: obtaining the final precursor film after 8-14 repeated spin coating and annealing of the precursor solution.
[0021] Preferably, the precursor film obtained by spin coating is subjected to high-temperature selenization, the selenization temperature is 550-570° C., and the time is 15-20 min.
[0022] A buffer layer, a window layer and an electrode are deposited on the CIGSSe absorption layer obtained as described above to prepare an antimony-doped copper indium gallium selenide sulfur thin film solar cell.
[0023] The beneficial effect of the method for preparing high-efficiency copper indium gallium sulfide selenide solar cells based on antimony doping by solution method provided by the present invention is that: compared with the prior art, the method for preparing high-efficiency copper indium gallium sulfide selenide solar cells based on antimony doping by solution method provided by the present invention avoids the generation of double grain layers by adding metal antimony salts of different concentrations to the precursor solution, thereby preparing a high-quality absorption layer with micron-level penetration, and thus the corresponding battery performance of the solar cell prepared based on this method is significantly improved. The present invention effectively solves the problem that the copper indium gallium selenide sulfide film prepared by the non-hydrazine solution method usually presents a double layer and poor quality, thereby limiting the improvement of device efficiency. At the same time, it is more convenient to dope by directly adding compound salts to the precursor solution, which can simplify the preparation process, reduce production costs, and facilitate large-scale commercialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 SEM images of CIGS precursor films prepared by doping metal antimony salts at different concentrations and then preparing the corresponding absorption layers by selenization; surface and cross-sectional images of the absorption layers obtained by selenization at different antimony doping concentrations;
[0026] Figure 2 XRD spectrum of the copper indium gallium selenide sulfur absorption layer film obtained by selenization with metal antimony salts doped with different concentrations (a), half width of the (112) peak of the XRD of the absorption layer film obtained by selenization with metal antimony salts doped with different concentrations;
[0027] Figure 3 Box plots showing the parameters of photovoltaic devices prepared by selenization of copper indium gallium selenide sulfur absorber films doped with different concentrations of metal antimony salts;
[0028] Figure 4 IV curves of the reference sample and the CIGS device obtained at the optimal antimony doping concentration. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] Please also read Figures 1 to 4 , a method for preparing a high-efficiency copper indium gallium sulfide selenide solar cell based on antimony doping by solution method provided by the present invention is now described. The method for preparing a high-efficiency copper indium gallium sulfide selenide solar cell based on antimony doping by solution method is to prepare a micron-scale vertically penetrating grain layer by adding metal antimony salts of different concentrations in a precursor solution, thereby preparing a high-efficiency copper indium gallium selenide sulfide thin film solar cell with a structure of SLG / Mo / CIGSSe / CdS / i-ZnO / ZnO:Al / Ag. Specifically, it includes the following steps:
[0031] S1. Prepare precursor solution.
[0032] Taking thiourea, copper acetate, indium trichloride tetrahydrate and anhydrous gallium chloride as raw materials, weigh out the drugs and add them into dimethylformamide solvent respectively.
[0033] 2-3M thiourea (99.0%), 0.4-0.5M copper acetate (99.95%), 0.3-0.4M indium chloride tetrahydrate (99.99%), and 0.1-0.2M anhydrous gallium chloride (99.99%) were sequentially added to dimethylformamide solvent to obtain a precursor solution. It should be noted that the molar ratio of thiourea to all metals is 2.5-3.
[0034] Specifically, the implementation of step 1 includes:
[0035] S1.1, add 2-3M thiourea into dimethylformamide solvent;
[0036] S1.2, after thiourea is completely dissolved in dimethylformamide solvent, add 0.4-0.5M copper acetate into the above clear solution;
[0037] S1.3, after the copper acetate is further dissolved, add 0.3-0.4M indium chloride tetrahydrate to the above reaction solution;
[0038] S1.4, after the indium chloride tetrahydrate is dissolved, anhydrous gallium chloride having a concentration of 0.1-0.2M is further added to the above solution;
[0039] S1.5. After the anhydrous gallium chloride is further completely dissolved, a uniform and stable CIGS precursor solution is obtained.
[0040] S2, adding metal antimony salt to the precursor solution for antimony doping, to prepare precursor solutions with different antimony doping amounts;
[0041] Specifically, different amounts of antimony salt (chloride or iodide) are added to the prepared CIGS precursor solution, and the present invention achieves antimony doping in the precursor solution by adding different amounts of antimony salt, wherein the molar concentration range of the antimony salt is 0-0.035M.
[0042] S3, spin coating the precursor solution and performing annealing operation, repeating for multiple times to obtain precursor films with different antimony doping concentrations;
[0043] In this step, during each spin coating annealing process, hot stage annealing and drying are adopted, the spin coating speed is 2000-3500 rpm, and the hot stage annealing temperature is 250-300°C.
[0044] In this step, the final precursor film needs to be repeatedly spin-coated 8-12 times so that the final prepared battery can fully absorb sunlight. The precursor solution is repeatedly spin-coated and then annealed to achieve the required thickness.
[0045] S4. After selenization treatment, a copper indium gallium selenide sulfur (CIGSSe) absorption layer is obtained; specifically, the CIGSSe absorption layer is obtained by selenization in a rapid annealing furnace, the selenization temperature is 550-570° C., and the time is 15-20 minutes.
[0046] S5, depositing a buffer layer, a window layer and an electrode to prepare a copper indium gallium selenide sulfur thin film solar cell. Specifically, a 50-80nm cadmium sulfide buffer layer is deposited by a chemical water bath method, a 50-100nm intrinsic zinc oxide and a 350-400nm aluminum-doped zinc oxide window layer are grown by a DC magnetron sputtering method, and a 1-1.5μm silver top electrode is prepared by a thermal evaporation method.
[0047] The present invention provides a method for preparing high-efficiency copper indium gallium selenide solar cells based on antimony doping by solution method. Compared with the prior art, the growth of the film during the selenization growth process is promoted by doping with antimony, thereby obtaining an absorption layer that penetrates from top to bottom, and at the same time, the number of defects in the absorption layer is passivated, thereby improving the transport efficiency of carriers. Finally, under standard test conditions, the efficiency of copper indium gallium selenide sulfur devices prepared by the solution method at different antimony doping concentrations is improved, and finally a copper indium gallium selenide sulfur device efficiency of 16.33% is obtained in a non-hydrazine dimethylformamide solvent system, which is at the leading level in the current literature records. At the same time, it should be pointed out that the process of the present invention is simple, and only simple antimony doping is performed in the precursor to obtain a high-quality copper indium gallium selenide sulfur absorption layer that penetrates from top to bottom at the micrometer level. The experimental process is simple, which lays a solid foundation for the further commercial development of high-efficiency copper indium gallium selenide sulfur cells prepared by the non-hydrazine solution method.
[0048] Embodiment 1,
[0049] A method for preparing a copper indium gallium sulfur selenide solar cell based on a solution process comprises the following steps:
[0050] S1. Prepare precursor solution.
[0051] 2.486 g of thiourea (CH4N2S, 99.0%), 1.047 g of copper acetate (Cu(CH3COO)2·H2O, 99.95%), 1.161 g of indium chloride tetrahydrate (InCl3·4H2O, 99.99%) and 0.296 g of anhydrous gallium chloride (GaCl3, 99.99%) were sequentially added into 12 mL of dimethylformamide solvent (C3H7NO, 98%) to prepare a stable and uniform precursor solution;
[0052] In this step, the drug to be added later needs to be added after the previous raw material has been completely reacted and dissolved. The molar ratio of thiourea to the sum of all metal salts is 3, so that thiourea can form a complete coordination with all metals.
[0053] S2. Spin coating the precursor solution and performing annealing operation, repeating the process multiple times to obtain a precursor film.
[0054] In each spin coating annealing process, hot stage annealing and drying are adopted, and the annealing temperature is 280°C. After 12 times of repeated spin coating and annealing of the precursor solution, the final precursor film is obtained.
[0055] S3. The CIGSSe absorption layer is obtained by selenization in a rapid annealing furnace at a selenization temperature of 570°C for 20 minutes, thereby obtaining a high-quality copper indium gallium selenide sulfur absorption layer that penetrates the grains.
[0056] S4, depositing a 50nm cadmium sulfide buffer layer, an 80nm zinc oxide and a 300nm aluminum-doped zinc oxide window layer and a 1μm silver electrode to prepare the final copper indium gallium selenide sulfur thin film solar cell.
[0057] Example 2
[0058] A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method comprises the following steps:
[0059] S1. Prepare precursor solution.
[0060] 2.486 g of thiourea (CH4N2S, 99.0%), 1.047 g of copper acetate (Cu(CH3COO)2·H2O, 99.95%), 1.161 g of indium chloride tetrahydrate (InCl3·4H2O, 99.99%) and 0.296 g of anhydrous gallium chloride (GaCl3, 99.99%) were sequentially added into 12 mL of dimethylformamide solvent (C3H7NO, 98%) to prepare a stable and uniform precursor solution;
[0061] In this step, the drug to be added later needs to have reacted before the previous raw material. The molar ratio of thiourea to the sum of all metal salts is 3. This allows all metals to form complete coordination with thiourea.
[0062] S2. doping the precursor solution with antimony.
[0063] Antimony trichloride is added to the prepared precursor solution to achieve antimony doping in the precursor solution, wherein the purity of the antimony trichloride is 99.9%; and the molar concentration range of the antimony trichloride is 0-0.035 mol / L.
[0064] Among them, in this embodiment, the calibration of different concentrations of antimony doping is mainly defined by the molar ratio (MSbCl3 / MCu(CH3COO)2·H2O) of antimony trichloride (SbCl3, 99.9%) and copper acetate (Cu(CH3COO)2·H2O, 99.95%), and antimony doping is performed at MSbCl3 / MCu(CH3COO)2·H2O=2%.
[0065] S3, spin coating the precursor solution and performing annealing operation, repeating the process multiple times to obtain a precursor film.
[0066] During each spin coating annealing process, a hot stage annealing and drying is used. The annealing temperature is 280°C. After 12 times of repeated spin coating and annealing of the precursor solution, the final precursor film is obtained.
[0067] S4. The CIGSSe absorption layer is obtained by selenization in a rapid annealing furnace at a selenization temperature of 570° C. for 20 min, thereby obtaining a high-quality copper indium gallium selenide sulfur absorption layer that penetrates the grains.
[0068] S5, depositing a 50nm cadmium sulfide buffer layer, an 80nm zinc oxide and a 300nm aluminum-doped zinc oxide window layer and a 1μm silver electrode to prepare the final copper indium gallium selenide sulfur thin film solar cell.
[0069] Embodiment 3,
[0070] A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method comprises the following steps:
[0071] S1. Prepare precursor solution.
[0072] A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method comprises the following steps:
[0073] S1. Prepare precursor solution.
[0074] 2.486 g of thiourea (CH4N2S, 99.0%), 1.047 g of copper acetate (Cu(CH3COO)2·H2O, 99.95%), 1.161 g of indium chloride tetrahydrate (InCl3·4H2O, 99.99%) and 0.296 g of anhydrous gallium chloride (GaCl3, 99.99%) were sequentially added into 12 mL of dimethylformamide solvent (C3H7NO, 98%) to prepare a stable and uniform precursor solution;
[0075] In this step, the drug to be added later needs to have reacted before the previous raw material. The molar ratio of thiourea to the sum of all metal salts is 3. All metals can form complete coordination with thiourea. S2. Antimony doping of the precursor solution.
[0076] Antimony trichloride is added to the prepared precursor solution to achieve antimony doping in the precursor solution, wherein the purity of the antimony trichloride is 99.9%; and the molar concentration range of the antimony trichloride is 0-0.035 mol / L.
[0077] Among them, in this embodiment, the calibration of different concentrations of antimony doping is mainly defined by the molar ratio (MSbCl3 / MCu(CH3COO)2·H2O) of antimony trichloride (SbCl3, 99.9%) and copper acetate (Cu(CH3COO)2·H2O, 99.95%), and antimony doping is performed at MSbCl3 / MCu(CH3COO)2·H2O=5%.
[0078] S3, spin coating the precursor solution and performing annealing operation, repeating the process multiple times to obtain a precursor film.
[0079] During each spin coating annealing process, a hot stage annealing and drying is used. The annealing temperature is 280°C. After 12 times of repeated spin coating and annealing of the precursor solution, the final precursor film is obtained.
[0080] S4. The CIGSSe absorption layer is obtained by selenization in a rapid annealing furnace at a selenization temperature of 570° C. for 20 min, thereby obtaining a high-quality copper indium gallium selenide sulfur absorption layer that penetrates the grains.
[0081] S5, depositing a 50nm cadmium sulfide buffer layer, an 80nm zinc oxide and a 300nm aluminum-doped zinc oxide window layer and a 1μm silver electrode to prepare the final copper indium gallium selenide sulfur thin film solar cell.
[0082] Example 4
[0083] A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method comprises the following steps:
[0084] S1. Prepare precursor solution.
[0085] 2.486 g of thiourea (CH4N2S, 99.0%), 1.047 g of copper acetate (Cu(CH3COO)2·H2O, 99.95%), 1.161 g of indium chloride tetrahydrate (InCl3·4H2O, 99.99%) and 0.296 g of anhydrous gallium chloride (GaCl3, 99.99%) were sequentially added into 12 mL of dimethylformamide solvent (C3H7NO, 98%) to prepare a stable and uniform precursor solution;
[0086] In this step, the drug to be added later needs to have reacted before the previous raw material. The molar ratio of thiourea to the sum of all metal salts is 3. This allows all metals to form complete coordination with thiourea.
[0087] S2. doping the precursor solution with antimony.
[0088] Antimony trichloride is added to the prepared precursor solution to achieve antimony doping in the precursor solution, wherein the purity of the antimony trichloride is 99.9%; and the molar concentration range of the antimony trichloride is 0-0.035 mol / L.
[0089] Among them, in this embodiment, the calibration of different concentrations of antimony doping is mainly defined by the molar ratio (MSbCl3 / MCu(CH3COO)2·H2O) of antimony trichloride (SbCl3, 99.9%) and copper acetate (Cu(CH3COO)2·H2O, 99.95%), and antimony doping is performed at MSbCl3 / MCu(CH3COO)2·H2O=8%.
[0090] S3, spin coating the precursor solution and performing annealing operation, repeating the process multiple times to obtain a precursor film.
[0091] During each spin coating annealing process, a hot stage annealing and drying is used. The annealing temperature is 280°C. After 12 times of repeated spin coating and annealing of the precursor solution, the final precursor film is obtained.
[0092] S4. The CIGSSe absorption layer is obtained by selenization in a rapid annealing furnace at a selenization temperature of 570° C. for 20 min, thereby obtaining a high-quality copper indium gallium selenide sulfur absorption layer that penetrates the grains.
[0093] S5, depositing a 50nm cadmium sulfide buffer layer, an 80nm zinc oxide and a 300nm aluminum-doped zinc oxide window layer and a 1μm silver electrode to prepare the final copper indium gallium selenide sulfur thin film solar cell.
[0094] Data Analysis:
[0095] Figure 1The surface and cross-sectional images of the absorption layer obtained by selenization at different antimony doping concentrations are shown in Figure 1. The surface grains of the 0Sb sample are relatively small, and the cross-sectional SEM shows that the absorption layer presents a double-layer grain. As the antimony doping concentration increases, the surface grains gradually become larger, and the absorption layer becomes a vertically penetrating grain layer. The 5Sb sample is the best. As the antimony doping concentration is further increased, although the grain size of the 8Sb sample increases slightly, the number of holes on the sample surface increases.
[0096] Figure 2 (a) is the XRD pattern of the absorption layer (0Sb, 2Sb, 5Sb and 8Sb) obtained at different antimony doping concentrations. All absorption layers show similar XRD patterns. Figure 2 (b) is the half-width of the (112) peak of different samples. As the antimony doping concentration increases, the half-width of the (112) peak corresponding to the copper indium gallium selenide sulfur absorption layer first decreases and then increases, indicating that the quality of the prepared copper indium gallium selenide sulfur absorption layer changes from bad to good and then to worse.
[0097] A 50nm cadmium sulfide buffer layer, an 80nm intrinsic zinc oxide and a 300nm aluminum-doped zinc oxide window layer were deposited on the absorption layer prepared based on different antimony doping concentrations, and finally a 1μm silver top electrode was deposited by thermal evaporation to prepare the final copper indium gallium selenide sulfur devices with different antimony doping concentrations, namely C-0Sb, C-2Sb, C-5Sb and C-8Sb. Figure 3 The box plots of battery statistics for C-0Sb, C-2Sb, C-5Sb and C-8Sb show that with the increase of antimony doping concentration, various parameters of the copper indium gallium selenide sulfur device first increase and then decrease, and C-5Sb obtains the optimal device parameters.
[0098] IV tests were performed on the reference samples and the devices obtained at the optimal antimony doping concentration, such as Figure 4 As shown, compared with the efficiency of 12.81% of the reference sample without antimony doping, the efficiency of the champion device at the optimal antimony doping concentration is 16.33%, an increase of 27.5%.
[0099] At a suitable antimony doping concentration, grain growth can be effectively promoted to obtain a micron-scale copper indium gallium sulfide selenide absorption layer that penetrates from top to bottom, effectively improving the quality of the absorption layer and inhibiting carrier recombination, and ultimately obtaining a copper indium gallium selenide sulfur device efficiency of 16.33%. The present invention provides a practical method for preparing high-efficiency copper indium gallium sulfide selenide by a non-hydrazine solution method.
[0100] Through research and development, the present invention avoids the generation of twin grain layers by adding different concentrations of metal antimony salts to the precursor solution, thereby preparing a high-quality absorption layer with micron-level penetration, and the corresponding battery performance of the solar cell prepared based on this method is significantly improved. The present invention effectively solves the problem that the copper indium gallium selenide sulfur film prepared by the non-hydrazine solution method usually presents a double layer and poor quality, thereby limiting the improvement of device efficiency. At the same time, it is more convenient to dope by directly adding compound salts to the precursor solution, which can simplify the preparation process, reduce production costs, and facilitate large-scale commercialization.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method, characterized in that: The following steps are involved: Preparing a precursor solution; Adding different amounts of metal antimony salts to the precursor solution for antimony doping; Spin coating a precursor solution and performing multiple annealing operations to obtain a precursor film; After selenization treatment, a copper indium gallium selenide sulfur absorption layer is obtained; A buffer layer, a window layer and an electrode are deposited to prepare an antimony-doped copper indium gallium selenide sulfur thin film solar cell.
2. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 1, characterized in that: The preparation of the precursor solution comprises: Weigh thiourea, copper acetate, indium trichloride tetrahydrate, and anhydrous gallium chloride respectively according to a preset ratio; Thiourea, copper acetate, indium trichloride tetrahydrate and anhydrous gallium chloride are sequentially added into a dimethylformamide solvent and stirred to dissolve, thereby obtaining a CIGS precursor solution.
3. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 1, characterized in that: The molar ratio of thiourea to the sum of all metal salts is 2.5-3.
4. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 1, characterized in that: The step of adding metal antimony salt to the precursor solution for antimony doping, thereby preparing CIGS precursor solutions with different doping concentrations, comprises: Antimony trichloride is added to the prepared CIGS solution, and antimony doping in the precursor solution is achieved by adding antimony trichloride of different masses. The molar concentration range of antimony trichloride is 0-0.035M.
5. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 1, characterized in that: The molar ratio of antimony trichloride to copper acetate is one or more of 0, 2%, 5% and 8%.
6. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 1, characterized in that: Spin coating precursor solutions with different antimony doping concentrations and performing annealing operations are repeated multiple times to obtain precursor films, including: The CIGS precursor solution was spin-coated on the molybdenum-coated glass and then annealed and dried using a hot stage.
7. The method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method according to claim 7, characterized in that: The precursor solution is spin-coated and annealed at a speed of 2000-3500 rpm and an annealing temperature of 250-300° C., and the process is repeated multiple times to obtain a precursor film, including: the final precursor film is obtained after 8-14 times of repeated spin coating and annealing of the precursor solution.
8. A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method as claimed in claim 1, characterized in that: The precursor film obtained by spin coating is subjected to high-temperature selenization, the selenization temperature is 550-570° C., and the time is 15-20 minutes.
9. A method for preparing high-efficiency copper indium gallium sulfur selenide solar cells based on antimony doping by solution method as claimed in claim 1, characterized in that: A buffer layer, a window layer and an electrode are deposited on the CIGSSe absorption layer obtained by selenization to prepare an antimony-doped copper indium gallium selenide sulfur thin film solar cell.
10. A copper indium gallium sulfur selenide solar cell, characterized in that: The method is prepared based on the steps of a method for preparing high-efficiency copper indium gallium sulfur selenide solar cells by antimony doping through a solution process as described in any one of the above items.
Citation Information
Cited By
Copper-vanadium-sulfur-selenium light absorption film and preparation method and application thereof
CN121449343A
